2019
DOI: 10.1371/journal.pone.0220305
|View full text |Cite
|
Sign up to set email alerts
|

Factorial calculation of calcium and phosphorus requirements of growing dogs

Abstract: Calcium and phosphorus requirements for growing dogs can be calculated by different methods. The current standard feeding recommendations are based on experimental data derived from young giant breed puppies. In order to determine the absolute requirement, an extrapolation via metabolisable energy requirement is recommended. Another approach is to calculate the requirement factorially, taking into account the endogenous losses and the amount of calcium and phosphorus retained due to tissue accretion during gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(33 reference statements)
0
3
1
Order By: Relevance
“…The wider Ca/P faecal ratio and decrease in ∆Ca/P imply that even though the source of phosphate did not differ between groups, more phosphate was digested in the HNaCl group. These results differ from previous findings by Böswald et al (2020), who found that highly soluble phosphates led to significantly lower ∆Ca/P values in dogs [ 72 ] but not in cats [ 73 ]. A possible explanation for the higher digestibility of phosphorus in our study could be from an increase in phosphate availability due to the high sodium chloride intake.…”
Section: Discussioncontrasting
confidence: 99%
“…The wider Ca/P faecal ratio and decrease in ∆Ca/P imply that even though the source of phosphate did not differ between groups, more phosphate was digested in the HNaCl group. These results differ from previous findings by Böswald et al (2020), who found that highly soluble phosphates led to significantly lower ∆Ca/P values in dogs [ 72 ] but not in cats [ 73 ]. A possible explanation for the higher digestibility of phosphorus in our study could be from an increase in phosphate availability due to the high sodium chloride intake.…”
Section: Discussioncontrasting
confidence: 99%
“…Kienzle & Burger [3] collected literature data on intake and faecal excretion of major minerals in horses to estimate the true digestibility for these nutrients. Such data is invaluable for factorial calculation of nutrient requirements [4][5][6] and may show whether other dietary factors influence mineral digestibility [1]. For the factorial calculation of nutrient requirements, it is necessary to establish a dataset of intake and excretion of the nutient in question.…”
Section: Introductionmentioning
confidence: 99%
“…Plays an important role in bone formation and development. Both deficiency and excess of Ca can lead to disorders in skeletal development [Dobenecker et al 2006, Mack et al 2015, Böswald et al 2019. Calcium deficiency can lead to pathological fractures.…”
Section: Microelements and Macroelementsmentioning
confidence: 99%